Sertipikat Elektronik: Transformasi Digital, Kepastian Hukum, dan Tantangan Implementasi dalam Sistem Administrasi Pertanahan di Gorontalo - Andhika, Trezy; Isa, Rusli (Media Hukum Indonesia (MHI), 2025)
The acceleration of digital transformation in Indonesia’s land administration has led to the adoption of electronic land certificates (sertipikat elektronik) as a form of public service modernization aimed at enhancing bureaucratic efficiency, service transparency, and legal certainty for landholders. At the regional level—particularly in Gorontalo City—the implementation of this policy is of special interest, as the area serves as the economic and administrative center of Gorontalo Province, characterized by high urbanization rates and active land transactions. This study aims to academically analyze the dynamics of electronic certificate implementation in Gorontalo City by examining regulatory aspects, institutional readiness, public understanding, and technological infrastructure. The research employs a normative-analytical approach based on a review of recent scholarly literature (2020–2025) and secondary empirical data from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and the Gorontalo City Land Office. The findings indicate that while the electronic land certificate policy offers significant potential to improve public service delivery and legal protection, its implementation in Gorontalo City remains constrained by structural challenges such as technological infrastructure capacity, limited human resources, gaps in public digital literacy, and suboptimal synchronization of land data systems. Therefore, the successful implementation of electronic certificates in Gorontalo City requires not only a robust legal foundation but also strong local policy support, bureaucratic preparedness, and heightened public awareness as service users.